Esophageal thermal lesions in radiofrequency ablation for atrial fibrillation: A prospective comparative study of thermal sensors. Issue 8 (20th June 2022) - Arai, Shuhei; Watanabe, Norikazu; Sugiyama, Hiroto; Gokan, Toshihiko; Yoshikawa, Kosuke; Nakamura, Yuya; Inokuchi, Koichiro; Chiba, Yuta; Onishi, Yoshimi; Onuki, Tatsuya; Asano, Taku; Kobayashi, Youichi; et al.
Abstract: Background: Esophageal thermal lesion (ETL) is a complication of radiofrequency ablation for atrial fibrillation (RFAF). To prospectively compare the incidence of ETL, we used two linear, five‐ and three‐sensor esophageal thermal monitoring catheters (ETMC5 and ETMC3). We also evaluated the predictors of ETL. Methods: Patients receiving their first RFAF ( n  = 106) were randomized into two groups, ETMC5 ( n  = 52) and ETMC3 ( n  = 54). Ablation was followed by esophagogastroduodenoscopy within 3 days. Results: Esophageal thermal lesion was detected in 7/106 (6.6%) patients (ETMC5: 3/52 [5.8%] vs. ETMC3: 4/54 [7.4%]; p = 1.0). The maximum temperature and number of measurements > 39.0°C did not differ between the groups (ETMC5: 40.5°C and 5.4 vs. ETMC3: 40.6°C and 4.9; p  = .83 and p  = .58, respectively). In ETMC5 group, the catheter had to be moved significantly less often (0.12 vs. 0.42; p  = .0014) and fluoroscopy time was significantly shorter (79.2 min vs. 101.7 min; p  = .0038) compared with ECMC3 group. The total number of ablations in ETMC5 group was significantly greater (50.2 vs. 37.7; p  = .030) and ablation time was significantly longer (52.1 min vs. 40.1 min; p  = .0039). Only body mass index (BMI) was significantly different between patients with and without ETL (21.4 ± 2.5 vs. 24.3 ± 3.4; p  = .022). Conclusions: The incidence of ETL was comparable between ETMC5 and ETMC3 groups; however, fluoroscopy time, total ablation time, and total number of ablations differed significantly. Lower BMI may increase the risk of developing ETL.